Work satisfaction and stress among Portuguese neonatologists - 2019 survey - Gustavo Rocha; Filipa Flôr-; Sara Almeida; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2022)
Introduction: Work satisfaction and stress for doctors working in Neonatal Intensive Care Units (NICU) depend on several factors. The purpose of this survey was to assess work satisfaction and stress of neonatologists in Portugal. Material and methods: Anonymous electronic survey, with 46 questions, sent by e-mail to all members of the Portuguese Society of Neonatology in 2019 (i.e., 205 neonatologists). Results: 92 (44.9%) questionnaires were analyzed. Respondents were mostly female, aged 50-59 years, married and with children, working at a level IIIB NICU linked to university teaching. Most classified their clinical activity as satisfactory and prestigious. They often feel tired due to overwork, and fatigue affects physical, mental and social health. Most consider that the annual vacation days are not enough. The most stressful reported aspects were the emergency services, dealing with death situations, deciding to withdraw care, and dealing with decisions on the threshold of viability. Most respondents consider the age between 50 and 59 years old as adequate to stop doing emergency service. Some adverse working conditions, low salaries and the unmet need for scientific activity promotion were complaints placed by a significant number of doctors. Discussion: The satisfaction level of neonatologists in Portugal is high. Emergency service is the main cause of stress. Overwork, low salaries, staff rejuvenation and scientific activity promotion are aspects that require a large investment. Conclusion: This survey contributes to the national characterization of work satisfaction and stress of neonatologists, which may inform policies and interventions targeted at the needs of this group of clinicians.